2002
DOI: 10.3727/000000002783985477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Size, Viability, and Function of Fetal Pig Islet-Like Cell Clusters after Digestion Using Collagenase or Liberase

Abstract: Liberase is a highly purified blend of collagenases that has been specifically developed to eliminate the numerous problems associated with the conventional use of crude collagenase when isolating islet-like cell clusters (ICCs) from pancreases of different species. The influence of Liberase on yield, size, viability, and function of ICCs has been documented when this enzyme was used to digest adult but not fetal pancreases. In this study, we compared the effects of collagenase and Liberase on fetal pig ICCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…We also suspect that Liberase has a gentler action than did standard crude collagenase preparations and may require a longer time to act. Indeed, other authors have reported longer digestion times for other tissues such as pancreas (35) and ovary (36) when using Liberase compared with standard collagenase.…”
Section: Discussionmentioning
confidence: 99%
“…We also suspect that Liberase has a gentler action than did standard crude collagenase preparations and may require a longer time to act. Indeed, other authors have reported longer digestion times for other tissues such as pancreas (35) and ovary (36) when using Liberase compared with standard collagenase.…”
Section: Discussionmentioning
confidence: 99%
“…Different protease activity was necessary for optimal tissue digest efficacy and cell yield [19, 2426]. However, the challenge is to balance the combination of enzymes and digesting time for the desired cell yield and function [27].…”
Section: Discussionmentioning
confidence: 99%
“…The method for extraction and purification of islets from the pig pancreas has undergone significant improvements and has been reported for fetal [15–17], neonatal [18,19], and adult pigs [20–23]. Insulin‐producing beta cells in fetal and neonatal pig pancreata are organized in cell clusters that lack a defined shape, unlike adult islets, and therefore are very difficult to separate from the exocrine pancreatic cells and other non‐islet cells of the pancreas.…”
Section: Introductionmentioning
confidence: 99%